2017
DOI: 10.1021/jacs.7b07918
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ultrafine and Highly Dispersed Metal Nanoparticles Confined in a Thioether-Containing Covalent Organic Framework and Their Catalytic Applications

Abstract: Covalent organic frameworks (COFs) with well-defined and customizable pore structures are promising templates for the synthesis of nanomaterials with controllable sizes and dispersity. Herein, a thioether-containing COF has been rationally designed and used for the confined growth of ultrafine metal nanoparticles (NPs). Pt or Pd nanoparticles (Pt NPs and Pd NPs) immobilized inside the cavity of the COF material have been successfully prepared at a high loading with a narrow size distribution (1.7 ± 0.2 nm). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
400
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 545 publications
(414 citation statements)
references
References 50 publications
1
400
0
2
Order By: Relevance
“…Notably,t he lattice spacing of MoS 2 in the doping composites is slightly larger than literature report( 0.62 nm), which is attributed to ion intercalation. [28][29][30][31][32][33][34][35] The nitrogen-containing triazine unit in the CTF skeleton can activate the electrons around the carbon,w hich will lead to an outstanding electrochemical performance. [27] Meanwhile, interplanars pacing of 0.27 nm is in accordance with the (1 00) Based on the above,C TFs@MoS 2 -X have ac rystal p-conjugated stacking architecture and hierarchical meso-and micropores in one hybrid system;t his fine structure is facile for fast p-electron hopping,m ass transfer,a nd confinement of the MoS 2 nanoparticles to facilitate large-particle growth.…”
Section: Resultsmentioning
confidence: 99%
“…Notably,t he lattice spacing of MoS 2 in the doping composites is slightly larger than literature report( 0.62 nm), which is attributed to ion intercalation. [28][29][30][31][32][33][34][35] The nitrogen-containing triazine unit in the CTF skeleton can activate the electrons around the carbon,w hich will lead to an outstanding electrochemical performance. [27] Meanwhile, interplanars pacing of 0.27 nm is in accordance with the (1 00) Based on the above,C TFs@MoS 2 -X have ac rystal p-conjugated stacking architecture and hierarchical meso-and micropores in one hybrid system;t his fine structure is facile for fast p-electron hopping,m ass transfer,a nd confinement of the MoS 2 nanoparticles to facilitate large-particle growth.…”
Section: Resultsmentioning
confidence: 99%
“…[49] A set of control experiments revealed that the crystallinity of the COF support and the presence of thioether groups inside the cavities are critical for the size-controlled synthesis of ultrafine NPs. Zhang and co-workers showed how COFs display the right combination of properties to serve as ideal host materials for size-controlled synthesis of nanoparticles, as demonstrated by entrapping Pt and Pb nanoparticles onto a thioether-containing COF.…”
Section: Catalysismentioning
confidence: 99%
“…Heterogeneous and homogeneous catalysts, especially metal nanoparticles (NPs) supported catalysts with excellent catalytic performance have attracted extensive interest in the last decade . Metal NPs exhibit excellent catalytic activity in organic reactions, such as nitro reduction, hydrogenation, CH activation, and coupling reactions .…”
Section: Methodsmentioning
confidence: 99%